Combined treatments with microballoon catheters and multiple cryoablation probes for shoulder-subclavian soft tissue hemangiopericytoma: A case report - Renato Argirò, MD, PhD; Giorgio Ciccarese, MD; Leonardo Vattermoli, MD; Sara Crociati, MD; Vincenzo Iannibelli, MD; Valentina Forte, MD; Daniele Morosetti, MD, PhD; Roberto Floris, MD, PhD (Radiology Case Reports, 2023)
We describe a case of a 65-year-old woman affected by hemangiopericytoma/solitary fibrous tumor of the right shoulder—subclavian region. Hemangiopericytoma/solitary fibrous tumor is a rare tumor of uncertain malignancy. She reports shoulder pain and inability to abduct the arm and elevate the shoulder. Imaging showed erosion of the scapula. The patient underwent 5 sessions of “on demand” embolization in the previous 2 years scheduled for recurrence of symptoms-swelling of tissues. Further 2 treatments were achieved through embolization via 2 different microballoon catheter combined with percutaneous cryoablation with 5 probes. Images after the treatment demonstrate a marked reduction in the hypervascularized area and an increase in the necrosis area. So, this combined treatment is safety and reproducible also in extrahepatic tissue.